Demand shocks, capacity coordination, and industry performance: lessons from an economic laboratory. - Hampton, Kyle; Sherstyuk, Katerina (RAND Journal of Economics (Wiley-Blackwell))
Antitrust exemptions granted to businesses under extenuating circumstances are often justified by the argument that they benefit the public by helping producers adjust to otherwise difficult economic circumstances. Such exemptions may allow firms to coordinate their capacities, as was the case of the post-September 11, 2001, antitrust immunity granted to Aloha and Hawaiian Airlines. We conduct economic laboratory experiments to determine the effects of explicit capacity coordination on oligopoly firms' abilities to adjust to negative demand shocks and on industry prices. The results suggest that capacity coordination speeds the adjustment process, but also has a clear procollusive effect on firm behavior.